2010
DOI: 10.1016/j.febslet.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 represses LXRα‐mediated transcriptional activity of SREBP‐1c promoter in HepG2 cells

Abstract: Edited by Robert BaroukiKeywords: SREBP-1c promoter FoxO1 LXRa Insulin a b s t r a c t Recent studies have demonstrated that FoxO1 modulates the expression of SREBP-1c, but the exact mechanism remains unknown. Our results demonstrate that FoxO1 suppresses the SREBP-1c promoter transcriptional activity in HepG2 cells. This repression was independent of FoxO1 binding to the SREBP-1c promoter, but LXR responsive elements (LXREs) were crucial to this phenomenon. Moreover, FoxO1 also strongly inhibited the LXRa-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In addition, our ChIP studies demonstrate that FoxO1 directly associates with the SREBP-1c promoter and that this association is regulated in a physiologic manner by insulin. Therefore, these studies support the hypothesis that FoxO1 contributes to the repression of SREBP-1c gene expression during fasting and/or insulin-deficient states (6,26,31). On the other hand, in conditions such as the metabolic syndrome, impaired suppression of FoxO1 may trigger an alternative activation of Akt signaling that can lead to increased hepatic lipid synthesis in the face of insulin resistance (7).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, our ChIP studies demonstrate that FoxO1 directly associates with the SREBP-1c promoter and that this association is regulated in a physiologic manner by insulin. Therefore, these studies support the hypothesis that FoxO1 contributes to the repression of SREBP-1c gene expression during fasting and/or insulin-deficient states (6,26,31). On the other hand, in conditions such as the metabolic syndrome, impaired suppression of FoxO1 may trigger an alternative activation of Akt signaling that can lead to increased hepatic lipid synthesis in the face of insulin resistance (7).…”
Section: Discussionsupporting
confidence: 76%
“…Although we and others have observed negative regulation of SREBP-1c by FoxO1 both in vitro and in vivo (6,26,31), others have reported that the constitutively active FoxO1 mutants induce SREBP-1c in vivo (7,40). These seemingly opposing effects of overexpressed constitutively active FoxO1 mutants may result from differences in genetic background of the animal models used, duration of treatment, levels of FoxO1 expressed, nutritional state, or differing characteristics of the FoxO1 mutants employed (6,7,40).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…FoxO1, generally known as an activator of gluconeogenic genes during fasting, can repress the transactivating ability of LXR and cooperating transcription factors SREBP1c and Specificity protein 1 (Sp1) to activate SREBP1c transcription during fasting (Liu et al, 2010;Deng et al, 2012). FoxO1 does not seem to bind directly to the SREBP1c promoter, but appears to act as a repressor through protein-protein interactions, possibly by recruiting CR proteins (Deng et al, 2012).…”
Section: Regulation By Foxo1mentioning
confidence: 99%
“…Another possible mechanism of insulin activation of LXR-mediated lipogenesis is its ability to inhibit the gluconeogenic transcription factor Forkhead box protein 1 (Foxo1) via phosphorylation and sequestration in the cytoplasm. As Foxo1 has been shown to inhibit LXR-mediated transactivation of the SREBP-1c promoter [19,20] , the insulin signal would relieve LXR and cooperating transcription factors from transrepression by Foxo1 allowing for full activation of SREBP-1c transcription [21] . Finally, as insulin plays a permissive role in determining the flux rate through glycolysis and glucose metabolic pathways, insulin is necessary for proper glucose utilization and O-GlcNAc signaling to LXR and other glucose-regulated proteins, including ChREBP.…”
mentioning
confidence: 99%